Self-reported Resistance Training Is Associated With Better HR-pQCT–derived Bone Microarchitecture in Vegan People - Wakolbinger-Habel, Robert; Reinweber, Matthias; König, Jürgen; Pokan, Rochus; König, Daniel; Pietschmann, Peter; Muschitz, Christian (The journal of clinical endocrinology and metabolism, 2022)
Abstract Context A plant-based lifestyle is a global trend; lower bone mineral density and increased fracture risk in vegan people are reported. Objective The primary objective was to assess trabecular and cortical bone microarchitecture in vegans and omnivores. Secondary objectives were to evaluate relationships between bone microarchitecture, nutrition parameters, and physical activity. Methods This was an observational study at the Medical Department II, St. Vincent Hospital (tertiary referral center for gastrointestinal, metabolic, and bone diseases, and teaching hospital of the Medical University of Vienna), including 43 healthy nonobese female and male subjects on a plant-based diet for at least 5 years, and 45 healthy nonobese female and male subjects on an omnivore diet for at least 5 years. The main outcome measures were the parameters of trabecular and cortical bone microarchitecture (high-resolution peripheral quantitative computed tomography), serum markers of bone turnover, nutrient intake (nutrition protocol), and self-reported resistance training (physical activity questionnaires). Results In the vegan group, trabecular and cortical structure were altered compared with omnivores. Vegans not reporting resistance training had diminished bone microarchitecture compared with omnivores not reporting resistance training. In vegans and omnivores reporting resistance training, bone structure was similar. In both vegan subgroups (resistance training and not resistance training), a small number of correlations between nutrient intake and bone microarchitecture were observed without a conclusive pattern. Conclusion Bone microarchitecture in vegans differed from matched omnivores but could not be explained solely by nutrient uptake. These differences were attenuated between the subgroups reporting resistance training. In addition to a well-planned diet, progressive resistance training on a regular basis should be part of the vegan lifestyle.